Hubungan Antara Kadar Kalsium Serum Dengan Keberhasilan Fisioterapi Pada Pasien Stroke Iskemik - Yulianti Ely; Andi Wardihan Sindrang; Audry Devisanty Wuysang (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Calcium plays an important role in nerve conduction, muscle contraction, and blood clotting. This study aims to determine the relationship of serum calcium levels with the success of physiotherapy in ischemic stroke patients. This study used a cross-sectional design with observational analytics, conducted for 3 months with a sample of 33 people. Based on data analysis, there is the influence of calcium on NIHSS scores, Barthel Index scores and MMT scores (P